Research Summary of Teaching Basic Chinese Conversation Class - Wiliam Wijaya (Bina Nusantara University, 2013)
Basic Chinese Conversation is a foundation for beginner learners. Beginner learners will learn how to pronounce voice and tone with aspirated and unaspirated sounds. Then they will learn vocabulary and basic grammar. Nevertheless in this step there are many problems in learning pronunciation, vocabulary, and grammar including other issues. With these problems, the writer has intensively read and analyzed materials about Indonesian Chinese language learners’ speech difficulties and problems, then searched for the solution.